Synthesis and thermal study of dual coordination compound of gadolinium (III) and chromium (III); MATEC Web of Conferences; Vol. 85 : Chemistry and Chemical Technology in XXI Century (CCT 2016) - Bobrovnikova A.; Cherkasova T.; Shirokolobova A.; Syskina A. A. Anna Aleksandrovna (2016, 2016)
Title screen